(untitled) (Bangladesh Critical Care Journal, 2013)
Objective: To assess compliance of Intensive Care Units (ICUs) of Bangladesh to the components of resuscitation & management bundles of Surviving Sepsis Campaign (SSC). Secondary objective was to assess the impact of compliance on mortality and to determine how its compliance & mortality compared with other Asian and Western countries. Design: Prospective Cohort study. Setting: 14 ICUs of Bangladesh. Participants: 65 adult patients with severe sepsis admitted into these ICUs in July 2009. The organizational characteristics of the participating centers, the patients baseline characteristics, the achievement of target within the resuscitation & management bundle & outcome data were recorded. Outcome: Compliance with the Surviving Sepsis Campaigns resuscitation (6 hrs) & management (24 hrs) bundles. Results: Hospital mortality in ICU patients of Bangladesh suffering from severe sepsis was 49·2%. It was significantly higher than countries reported. Compliance to entire components of both resuscitation & management bundles were reported to be zero in ICUs of Bangladesh. Compliance of individual components of the bundles did not predict improved survival. Conclusion: In ICUs of Bangladesh, high mortality of severe sepsis and failure of compliance of SSC bundle guidelines to have positive impact on survival were presumably attributed to delayed diagnosis, poor adherence to & delayed application of SSC guidelines on sepsis bundles. DOI: http://dx.doi.org/10.3329/bccj.v1i1.14359 Bangladesh Crit Care J March 2013; 1: 8-17